UPAYA PEMBAHARUAN HUKUM ACARA PERDATA DALAM PEMBANGUNAN HUKUM NASIONAL MELALUI PERKEMBANGAN ALAT BUKTI ELEKTRONIK - Kadek Endra Setiawan; I Wayan Suka Antara Yasa (Jurnal Yustitia, 2026)
Along with the advancement of information technology and telecommunications, the trade that is carried out electronically is also growing. As a result, evidence has developed with the emergence of electronic evidence which is an extension of valid evidence in accordance with the applicable procedural law in Indonesia. The purpose of writing this scientific journal is intended to better understand the urgency of civil procedure law reform in national legal development and the development and implications of evidence reform in civil procedure law reform. The research method used in this research is normative research method with legislative approach and conceptual approach. The result of this research is the urgency of civil procedure law reform in the development of national law is in the context of development in the field of law and efforts to improve national legal development, in addition to supporting the achievement of legal certainty. Electronic evidence has been regulated in the Company Documents Law and the ITE Law, but the two laws are not sufficient to meet the interests of practice related to proof using electronic evidence in resolving civil disputes to the court. Therefore, it is necessary to change the system of evidence in the settlement of disputes through the courts from a closed system to an open system in Indonesia through the reform of the national civil procedure law.